Acupuncture therapy for drug addiction. Issue 1 (December 2016) - Motlagh, Farid; Ibrahim, Fatimah; Rashid, Rusdi; Seghatoleslam, Tahereh; Habil, Hussain
Abstract Acupuncture therapy has been used to treat substance abuse. This study aims to review experimental studies examining the effects of acupuncture on addiction. Research and review articles on acupuncture treatment of substance abuse published between January 2000 and September 2014 were searched using the databases ISI Web of Science Core Collection and EBSCO's MEDLINE Complete. Clinical trial studies on the efficacy of acupuncture therapy for substance abuse were classified according to substance (cocaine, opioid, nicotine, and alcohol), and their treatment protocols, assessments, and findings were examined. A total of 119 studies were identified, of which 85 research articles addressed the efficacy of acupuncture for treating addiction. There were substantial variations in study protocols, particularly regarding treatment duration, frequency of electroacupuncture, duration of stimulation, and choice of acupoints. Contradictory results, intergroup differences, variation in sample sizes, and acupuncture placebo effects made it difficult to evaluate acupuncture effectiveness in drug addiction treatment. This review also identified a lack of rigorous study design, such as control of confounding variables by incorporating sham controls, sufficient sample sizes, reliable assessments, and adequately replicated experiments.